2018
DOI: 10.4274/mirt.49368
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Impact Evaluation of Left Ventricular Systolic Parameters in Myocardial Perfusion Gated SPECT with 16 Frame and 8 Frame Acquisition Models

Abstract: Objective:Evaluating the effects of heart cavity volume, presence and absence of perfusion defect, gender and type of study (stress and rest) on the difference of systolic parameters of myocardial perfusion scan in 16 and 8 framing gated SPECT imaging.Methods:Cardiac gated SPECT in both 16 and 8 framing simultaneously and both stress and rest phases at one-day protocol was performed for 50 patients. Data have been reconstructed by filter back projection (FBP) method and left ventricular (LV) systolic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…They concluded that variables derived from the 16-frame gated images were suitable for clinical use. 9,12,13 New Knowledge Gained: According to our assessment, the LV diastolic functional indices derived from the 16-frame GMPS can be valuable in the serial follow-up and monitoring of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that variables derived from the 16-frame gated images were suitable for clinical use. 9,12,13 New Knowledge Gained: According to our assessment, the LV diastolic functional indices derived from the 16-frame GMPS can be valuable in the serial follow-up and monitoring of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that variables derived from the 16-frame gated images were suitable for clinical use. 9 12 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the association between possible perfusion abnormalities and cardiac iron overload should be investigated in future studies using state-of-the-art technologies like positron-emission tomography-MRI. In addition, for a more accurate assessment of diastolic dysfunction in cardiac gated SPECT for comparison with echocardiography, it is better to use 16 frames per cardiac cycle instead of 8 frames per cardiac cycle,[ 18 ] but it was not done in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for a more accurate assessment of diastolic dysfunction in cardiac gated SPECT for comparison with echocardiography, it is better to use 16 frames per cardiac cycle instead of 8 frames per cardiac cycle, [18] but it was not done in the present study.…”
Section: Discussionmentioning
confidence: 99%